Phenomenological Study of Nurses' Experiences in Performing Basic Life Support Actions for Palliative Patients - Pramono, Wijanarko Heru; Sugiyanto, Emilia Puspitasari; Prasetya, Chandra Hadi; Winda, Evi (Journal of Language and Health, 2024)
Patients who are in a state that cannot be cured due to the disease they suffer from (terminal state) and medical actions are futile (futile) can be stopped or postponed life support therapy, this term is often called Do Not Resuscitate (DNR) . The purpose of this study was to determine the experience of nurses in carrying out DNR actions for palliative patients in the dahlia room of Adiyatma Hospital, MPH, Central Java Province. The qualitative research method, there were 4 respondents who had met the inclusion criteria, including this research method using the indep interview technique. The results of the study obtained 2 themes, including the legal aspect of DNR actions, and the Ethical Aspect of DNR actions consisting of 4 ethical standards of beneficence, maleficence, autonomy, and justice. The focus of care given to palliative patients with DNR status is to prepare patients to face death well, feel free from pain, die comfortably, feel valuable, respected, feel peaceful, calm. Further research suggestions are the factors underlying DNR decision making for palliative patients.